15 sibling stories [videorecording (DVD)] - Kratt, Martin; Jacobson, Mary, (Screenwriter); Rodriguez, Nick, (Screenwriter) (PBS Kids, 2024)
Celebrate siblings with this collection of family-focused tales all about brothers and sisters. Alma tries to be a 'super sister' to Junior, and Arthur offers to babysit so his parents can relax. Then, when Margaret can't attend her first Thank You Day, Daniel brings the celebration to her.